GROWTH AND DEVELOPMENT OF Ipomoea WEEDS - Barroso, A. A. M. (2019)
Weeds reduce the productive potential of crops. Plants of the Ipomoea genus, besides competing for water, light, space and nutrients, create problems in crop harvests due to their volatile stems. The objective of this work was to evaluate the growth and development of five Ipomoea species. For such, Ipomoea grandifolia, Ipomoea hederifolia, Ipomoea nil, Ipomoea purpurea and Ipomoea quamoclit plants were analyzed during the summer and winter season. Five destructive and periodic growth evaluations were carried out for each study, where leaf number, leaves, stems, roots and the total biomass were analyzed. Phenological stages of the plant development were also evaluated for emergence, flowering and maturation subperiods by degree-days, totalizing five treatments, conducted in a completely randomized design with four replicates. The phonology averages were analyzed according to the Hess scale, and the growth data through nonlinear regressions. I. quamoclit and I. grandifolia obtained the highest number of leaves in the summer and the winter, respectively. I. nil obtained greater accumulation of leaf and stem dry biomass in both seasons. I. grandifolia obtained greater root development in both periods. I. quamoclit presented reduced cycle times when compared to the other species, especially I. hederifolia and I. grandifolia, which presented larger cycles. Based on the results, I. grandifolia probably shows greater interference with agricultural crops due to high root growth, high leaf production and longer cycle. Shorter-cycle species, such as I. quamoclit, when present, should require shorter residual control periods.